Composition Plans in Action: poetics of everyday possibilities - Rabelo, Flávio; Ferracini, Renato; Reis (Universidade Estadual de Campinas – UNICAMP, Campinas/SP, Brazil), Bruna (Revista Brasileira de Estudos da Presença, 2022)
This paper discusses the notion of performative action as compositional plans in action, shifting the idea of presence to relational processes in which the intensity of lived experience is refreshed in the game framed in each moment. To this end, we draw from a research experience developed by Núcleo Fuga! as a creative process that aims to engender framings that strain the bond between real and fictional. Hence, in a flow from the chosen procedures, artists and public articulate enticements and modes of relationship mediated by hybrid poetics of dance, theater and performance, intending, as consequence, to open the senses to the instant dramaturgies that habit offers. That process is fed by the underlying assumption that Real and Fiction are overlapping plans in a virtual space in which poetic action is refreshed by the artists at play, shooting cartographic compositions supported by the relations between body, environment and dramaturgy.